Studi Kemampuan Berkomunikasi Anak Usia Dini di TK Nurul Huda Selayar Sakra Barat Kabupaten Lombok Timur - Endriani, Ani (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2015)
The purpose of this study is to determine the ability of communicating early childhood in kindergarten Nurul Huda Selayar Sakra West Lombok Timur. The population in this study were all students who aged 5-6 years in kindergarten Nurul Huda Selayar which amounted to 30 students. Data collection technique using observation techniques as the principal method, and documentation as a complementary method. while the data analysis techniques using the formula percentage. From the analysis result that ability Communicating Early Childhood at Nurul Huda Kindergarten Selayar Sakra West Lombok Timur is in the category "Enough" with 65.33% percentage.